Fruit-growing family farms in the cities of Itatiba, Louveira, Valinhos and Vinhedo (SP): Socialeconomic and cultural aspects in the regional context of São Paulo state - Bredariol, Márcio Adriano (GEOUSP Espaço e Tempo (Online), 2022)
The article discusses the importance of family farming focused on the production of fruit, for the cities of Itatiba, Louveira, Valinhos and Vinhedo (SP). In the rural areas of these cities, it is possible to find a large number of small rural properties, formed from the disintegration of large coffee farms during the 1920s. In these properties, family-type relationships predominate, with the presence of the cultural heritage coming from the tradition of immigrants who arrived and settled in this region of the state of São Paulo between the end of the 19th century and the beginning of the 20th century. This region developed based on an agrarian economy focused on the production of fruits such as persimmon, grapes, figs, and guava, which are directly related to the regional social and economic organization.